Peran Identitas Agama Terhadap Niat Menggunakan Kosmetik Halal : Perluasan Theory of Planned Behavior - Nugroho, Anton Priyo; Izzat, Dzulfikar; Suhasti, Wuri (Universitas Ahmad Dahlan, 2019)
Market share of halal cosmetics in Indonesia increased all of the time. It was not surprising, as a country with the biggest Moslem population in the world, the need of halal cosmetics is a must. Had it trued that the consumption of halal cosmetics driven by religion (Islam) as a social identity or by other factors. This study tried to find the role of religion as consumer?s social identity with extended theory planned behavior. This study used purposived sampling technics among 100 collage students in Yogyakarta and analyzed with partial Least Square (PLS)s-SEM used smartPLS software. This research found that religion identity was not influenced toward intention to use cosmetics halal. The other variables, attitude, subjective norm and perceived behavior control have a positive and significant influenced toward intention to use halal cosmetics.